Peranan Pramuka Terhadap Pembentukan Karakter Peserta Didik - Nia Afrilda Nasution; Imam Sholeh Rambe; Dwi Anatasia Br. Ginting; Navatika Vivayosa Br. Surbakti; Fajar Sidik Siregar (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The purpose of this research is to discover various moral principles that can be instilled by teachers outside the classroom, methods that can be used by teachers to teach students character, and obstacles to teaching character in this context. This qualitative study uses interviews, observations, and written notes. Interactive data analysis includes collection, presentation, reduction and drawing conclusions. This research found that scout involvement outside the classroom can help form nine traits, namely commitment to religious beliefs, discipline, caring, concern for the environment, tolerance, honesty, creativity, independence and responsibility. There are four scouting approaches that can help change a child's personality during scout education. Both types of group systems, working together and competing, encourage students to be loyal and able to train themselves to be responsible people, and value time more to complete tasks. Three interesting and challenging activities stimulate students' interest so they try to do it themselves. Learning through action also makes it easier for students to gain knowledge so they can quickly analyze and understand what they learn. The four open environment activities teach children to be independent, survive, adapt, and follow rules. Schools must face challenges to children's character development, including factors such as unfavorable societal influences, the influence of globalization, and the level of parental education.